The F-box protein FBXL-5 governs vitellogenesis and lipid homeostasis in C. elegans - Breen, Peter C.; Kanakanui, Kendall G.; Newman, Martin A.; Dowen, Robert H. (Frontiers in Cell and Developmental Biology, 2024)
The molecular mechanisms that govern the metabolic commitment to reproduction, which often occurs at the expense of somatic reserves, remain poorly understood. We identified the Caenorhabditis elegans F-box protein FBXL-5 as a negative regulator of maternal provisioning of vitellogenin lipoproteins, which mediate the transfer of intestinal lipids to the germline. Mutations in fbxl-5 partially suppress the vitellogenesis defects observed in the heterochronic mutants lin-4 and lin-29, both of which ectopically express fbxl-5 at the adult developmental stage. FBXL-5 functions in the intestine to negatively regulate expression of the vitellogenin genes; and consistently, intestine-specific over-expression of FBXL-5 is sufficient to inhibit vitellogenesis, restrict lipid accumulation, and shorten lifespan. Our epistasis analyses suggest that fbxl-5 functions in concert with cul-6, a cullin gene, and the Skp1-related gene skr-3 to regulate vitellogenesis. Additionally, fbxl-5 acts genetically upstream of rict-1, which encodes the core mTORC2 protein Rictor, to govern vitellogenesis. Together, our results reveal an unexpected role for a SCF ubiquitin-ligase complex in controlling intestinal lipid homeostasis by engaging mTORC2 signaling.